The gender and social distance effects on compliment responses: a case-study on Jordanian Arabic Speakers (JAS) / Mohammad Mahmoud Abu Alsallal, Haliza Harun and Ramiaida Darmi - Abu Alsallal, Mohammad Mahmoud; Harun, Haliza; Darmi, Ramiaida (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This study aimed at determining the effects of gender and social distance on the social compliment responses of the Jordanian Arabic speakers (JAS). Therefore, the study adopted one research question which is “how does the gender and social distance affect the JAS’s compliment responses?” A descriptive research design was adopted for this study based on a sample comprised ten Jordanian Arabic speakers; five males and five females. The instrument of this study adopted a discourse completion test (DCT) based on ten different situations. The DCT included three strategies of responses: agreement, non-agreement and other interpretation. The responses of the (DCT) were analyzed quantitatively - using percentages and frequencies. The findings proved that there was a slight difference between males and females in their responses towards the social situations. Males practiced agreement compliment responses more than females as (86%) of compliment responses were given by males whereas (70 %) were given by females. In addition, participants gave more agreement compliment strategy responses in non-social situation (86%) than social situations (68%). The qualitative analysis proved that the participants practiced all the three strategies of compliment in the different social situations. Furthermore, Males were more active and responsive than females in practicing the speech act of compliment in social context. To add, females were more inclined to give non-agreement and other interpretation responses in the given social situations. The study suggested doing further research on the effects of gender and social distance on Arabic Speakers’ compliment responses in social situations.